2015
DOI: 10.1093/annonc/mdu568
|View full text |Cite
|
Sign up to set email alerts
|

Role of circulating tumor cells as prognostic marker in resected stage III colorectal cancer

Abstract: CTC detection was not associated with worse DFS and OS in patients with stage III CRC. Given the scarcity of CTC in these patients, it is likely that CTC determined by CellSearch system does not have a prognostic role in this setting. However, a longer follow-up is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 17 publications
3
43
0
Order By: Relevance
“…In addition, patients with detectable CTC have a significantly higher risk to develop a recurrent disease. Interestingly, the detection of CTC did not correlate with lymph node metastases, which is in line with previous reports [19, 36]. Furthermore, in our study population we were not able to prove a prognostic influence of detectable CTC or DTC in early stage (UICC stage II) patients.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, patients with detectable CTC have a significantly higher risk to develop a recurrent disease. Interestingly, the detection of CTC did not correlate with lymph node metastases, which is in line with previous reports [19, 36]. Furthermore, in our study population we were not able to prove a prognostic influence of detectable CTC or DTC in early stage (UICC stage II) patients.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, some large‐scale meta‐analyses have shown the prognostic significance of CTCs detected using the CellSearch system in metastatic breast cancer or CRC (Bidard et al., 2014; Lv et al., 2015; Huang et al., 2014). In contrast, a recent large study using this system showed that there was no prognostic significance of CTCs in CRC (Sotelo et al., 2015). Pantel et al.…”
Section: Markers Of Ctcs In the Pb Or Bm And Clinical Significance Ofmentioning
confidence: 87%
“…Furthermore, some large-scale meta-analyses have shown the prognostic significance of CTCs detected using the CellSearch system in metastatic breast cancer or CRC Lv et al, 2015;Huang et al, 2014). In contrast, a recent large study using this system showed that there was no prognostic significance of CTCs in CRC (Sotelo et al, 2015). Pantel et al (2012) reported that the CellSearch system gave false-positive results in patients with benign colorectal diseases, such as inflammatory colon diseases, and demonstrated that further molecular characterization of circulating epithelial cells was needed for the use of this CTC testing modality (Pantel et al, 2012).…”
Section: ) Immunocytologymentioning
confidence: 99%
“…CTCs comprise a low percentage of circulating cells commonly present in cancer patients. With numbers as low as one CTC per 10 6 −10 7 peripheral blood leukocytes, enrichment, investigation, and quantification of CTCs has proven extremely difficult [5], but the effort has been validated by current studies showing that the presence of CTCs in peripheral blood is a valuable prognostic marker in cancer patients [6, 7, 8, 9, 10, 11, 12], and an useful predictor of progression-free and overall survival. Results from clinical studies have shown breast, prostate and colorectal cancer patients with fewer CTCs in their peripheral blood survived longer than those with more CTCs [7, 8, 13].…”
Section: Introductionmentioning
confidence: 99%